Extracellular Vesicles as an Advanced Delivery Biomaterial for Precision Cancer Immunotherapy. Issue 5 (1st July 2021) - Ruan, Shaobo; Greenberg, Zachary; Pan, Xiaoshu; Zhuang, Pei; Erwin, Nina; He, Mei
Abstract: In recent years, cancer immunotherapy has been observed in numerous preclinical and clinical studies for showing benefits. However, due to the unpredictable outcomes and low response rates, novel targeting delivery approaches and modulators are needed for being effective to more broader patient populations and cancer types. Compared to synthetic biomaterials, extracellular vesicles (EVs) specifically open a new avenue for improving the efficacy of cancer immunotherapy by offering targeted and site‐specific immunity modulation. In this review, the molecular understanding of EV cargos and surface receptors, which underpin cell targeting specificity and precisely modulating immunogenicity, are discussed. Unique properties of EVs are reviewed in terms of their surface markers, intravesicular contents, intrinsic immunity modulatory functions, and pharmacodynamic behavior in vivo with tumor tissue models, highlighting key indications of improved precision cancer immunotherapy. Novel molecular engineered strategies for reprogramming and directing cancer immunotherapeutics, and their unique challenges are also discussed to illuminate EV's future potential as a cancer immunotherapeutic biomaterial. Abstract : Cancer immunotherapy is the game changer in treating cancers. However, only a small population of patients can respond well, which highlights the urgent need of novel immunity modulators. Extracellular vesicles as the natural biomaterial open a new avenue for improving the efficacy of cancer immunotherapy by offering targeted and site‐specific immunity modulation.